Low Carbon Growth Country Studies--Getting Started : Experience from Six Countries - World Bank (Washington, DC, 2014)
Six emerging economies, Brazil, China, India, Indonesia, Mexico, and South Africa, are proactively seeking to identify opportunities and related financial, technical, and policy requirements to move towards a low carbon growth path. With the help of the Energy Sector Management Assistance Program (ESMAP), the governments of these countries have initiated country-specific studies to assess their development goals and priorities, in conjunction with greenhouse gas (GHG) mitigation opportunities, and examine the additional costs and benefits of lower carbon growth. Mitigation actions today are expected to reduce future expenditure on adaptation. These actions can help attract international concessional funding to co-finance programs in energy, industry, transport, and natural resource management, which have carbon reduction implications. This paper illustrates the framework and the steps to perform a comprehensive assessment of GHG mitigation options, highlighting the central importance of sustained communication with stakeholders in the study process.